(untitled) (Andamios, Revista de Investigación Social, 2025)
In this paper, I present a catalog of the popular animal tales found in the literary fables of Spanish-American authors from the 18th to the early 20th centuries. After indexing more than fifty fables with parallels in oral storytelling, I conclude that many likely originate from an Indo-European written legacy, with the exception of a few tales with possible folkloric inspiration. I include a commentary on the animal rights and environmentalist messages embedded in the texts, in line with the concerns of contemporary academic currents, as well as a reflection on their connection with other genres, illustrated with examples from this corpus.